Numerical simulation of confined flows past obstacles – the comparative study of Lattice Boltzmann and Spectral Element Methods - Regulski, W.; Szumbarski, J. (Archives of Mechanics, 2012)
This paper concerns the Lattice Boltzmann Method (LBM) which has recently become alternative, computationally efficient tool to simulate a Newtonian fluid flow, especially in complex geometries. A series of benchmark two-dimensional simulations with the LBM are presented and analyzed in order to assess the impact of the LBM grid refinement on the results of the simulations. The considered cases include stationary and time-dependent flows past a circular or a 45-degree rotated square cylinder confined in the channel with parallel walls. Next, the same flow configurations are investigated by means of the Spectral Element Method (SEM) and obtained results are used to cross-validate both approaches. The sensitivity to the resolution of representation of the obstacle’s shape in the LBM simulations is of the main interest. Particular attention is paid also to the effects of compressibility of the flow. Additionally, for unsteady flows the transient flow characteristics are compared in detail: the velocity profiles from the LBM and SEM are presented and some non-dimensional characteristics such as Strouhal number of the compared von Karman vortex streets.